Training Future Citizens through Audiovisual Resources: Socio-educational Training and Social Responsibility of Students in Nothern Peru - Polo Escobar, Benjamín Roldan; Macalopú Rimachi, Jessica; Chávez Bejarano, Denis Guizela; Mendoza Zuta, Jannie Caroll (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Audiovisual resources are positioned as innovative pedagogical tools with high potential to transform socio-educational training and promote social responsibility among students. By analysing 120 students, the study found that integrating audiovisual materials in the classroom improves academic understanding and increases students' awareness and participation in social responsibility issues. The research highlights the importance of incorporating audiovisual resources into the educational curriculum to cultivate critical and engaged citizens who understand the impact of their actions on society. These findings support the importance of modernising educational practices to help students navigate contemporary social challenges effectively. The study contributes valuable insights into the role of audiovisual tools in promoting student development and social consciousness within the educational sphere.